Questions in Teaching and Learning Management of Lao Language Teaching in High School - NANTHAVONG, Vandthong (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
The purpose of this research was analyzed the question sentences in Lao language instruction in high school. Question sentences were selected in reading part of high school in 2022. The qualitative research method was used in this research. Three teachers’ guide books of Lao language in 2022 with 48 questions were selected for collection data by analyzing the word style, position words of question of Lao language teaching instruction. The timetable for recording of qestion sentences was used in this research. The results of research found that: 1) The style of words in question expressions that ask about one thing and many things. words in question expressions related to the answer of something have 3 words: "what", "how", "why" and words in question expressions related to multiple answers have 7 words: "what", "what kinds", "what are the important points". "How?" "What kind of story", "What kind of thing", "What kind of style". 2) The position of words in question were appeared in 2 positions: and words in question at the beginning of the sentence ask about only one thing in which there is only 1 word such as: "Why" ,while words in question at the end of the sentence have 2 types ask about one and ask about many things which have a total of 9 words such as: "what", "how", "what", "what is important", "what is the important point". "How?" "What kind of story", "What kind of thing", "What kind of style".